Paeoniflorin mitigates high glucose-induced lifespan reduction by inhibiting insulin signaling in Caenorhabditis elegans - Liu, Tianwen; Zhuang, Ziheng; Wang, Dayong (Frontiers in Pharmacology, 2023)
In organisms, high glucose can cause several aspects of toxicity, including the lifespan reduction. Paeoniflorin is the major component of Paeoniaceae plants. Nevertheless, the possible effect of paeoniflorin to suppress high glucose toxicity in reducing lifespan and underlying mechanism are largely unclear. Thus, in this study, we examined the possible effect of paeoniflorin in suppressing high glucose (50 mM)-induced lifespan reduction and the underlying mechanism in Caenorhabditis elegans. Administration with 16-64 mg/L paeoniflorin could prolong the lifespan in glucose treated nematodes. Accompanied with this beneficial effect, in glucose treated nematodes, expressions of daf-2 encoding insulin receptor and its downstream kinase genes (age-1, akt-1, and akt-2) were decreased and expression of daf-16 encoding FOXO transcriptional factor was increased by 16-64 mg/L paeoniflorin administration. Meanwhile, the effect of paeoniflorin in extending lifespan in glucose treated nematodes was enhanced by RNAi of daf-2, age-1, akt-1, and akt-2 and inhibited by RNAi of daf-16. In glucose treated nematodes followed by paeoniflorin administration, the increased lifespan caused by daf-2 RNAi could be suppressed by RNAi of daf-16, suggesting that DAF-2 acted upstream of DAF-16 to regulate pharmacological effect of paeoniflorin. Moreover, in glucose treated nematodes followed by paeoniflorin administration, expression of sod-3 encoding mitochondrial Mn-SOD was inhibited by daf-16 RNAi, and the effect of paeoniflorin in extending lifespan in glucose treated nematodes could be suppressed by sod-3 RNAi. Molecular docking analysis indicated the binding potential of paeoniflorin with DAF-2, AGE-1, AKT-1, and AKT-2. Therefore, our results demonstrated the beneficial effect of paeoniflorin administration in inhibiting glucose-induced lifespan reduction by suppressing signaling cascade of DAF-2-AGE-1-AKT-1/2-DAF-16-SOD-3 in insulin signaling pathway.